2005
DOI: 10.1093/carcin/bgi257
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interaction: the role of SULT1A1 and CYP3A5 polymorphisms as risk modifiers for squamous cell carcinoma of the oesophagus

Abstract: An imbalance in the activities of enzymes involved in the metabolism, conjugation and transport of xenobiotics may account for the variability in susceptibility to the development of complex diseases such as cancer between different population groups. In this study we investigated a functional polymorphism in the SULT1A1 gene in 245 patients and 288 controls. Previous studies have shown that the 638G-->A polymorphism that results in the substitution of arginine by histidine at codon 213 (SULT1A1*2) results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…The role of SULT1A1 in the biotransformation of tobacco carcinogens and its association with lung cancer has been previously reported (Liang et al, 2004). There are reports of SULT1A1*2 association with increased risk for oesophageal cancers (Dandara et al, 2006) as well as gastric cancer (Boccia et al, 2005) in individuals who consume alcohol and smoke tobacco.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The role of SULT1A1 in the biotransformation of tobacco carcinogens and its association with lung cancer has been previously reported (Liang et al, 2004). There are reports of SULT1A1*2 association with increased risk for oesophageal cancers (Dandara et al, 2006) as well as gastric cancer (Boccia et al, 2005) in individuals who consume alcohol and smoke tobacco.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to the GST super family of enzymes that have been studied extensively for tobacco carcinogenesis (Nakajima et al, 1995;Cheng et al, 1999;Buch et al, 2002;Jhavar et al, 2004Jhavar et al, , 2005, other phase II metabolising enzymes such as the SULT have been less extensively studied (Hung et al, 2004;Dandara et al, 2006;Pachouri et al, 2006). There also has not been any collation of published data or a meta-analysis of case -control studies evaluating SULT enzyme in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ECRG1 (Arg290Gln) was identified as the susceptible SNP of ESCC . It has been found that the increased risk of ESCC relates to combined SULT1A12*2 genotype and CYP3A5 heterozygous genotypes, especially in tobacco smokers (Dandara et al, 2006). SNP of ATP-binding cassette sub-family B (MDR/TAP) member 1 gene (ABCB1) was reported to be associated with lymph node and distant metastases in EC (Narumiya et al, 2011).…”
Section: Effects Of Mutations and Snps In Esophageal Cancermentioning
confidence: 99%